2018
DOI: 10.1002/ecs2.2512
|View full text |Cite
|
Sign up to set email alerts
|

The effects of urbanization and land use on ragweed distribution

Abstract: Quantifying the spatial distribution of allergenic plants within landscapes could help target management efforts and predict human exposure to allergens at a scale relevant to human activity. We analyzed the combined effects of urbanization (proxied by surrounding impervious surface area) and land use on the distribution of common ragweed (Ambrosia artemisiifolia, Asteraceae), a major contributor to hay fever and asthma through its production of allergenic pollen. Along urban‐to‐rural transects in three region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Indeed, suitable climatic conditions are spread throughout Europe in all time frames considered, even though with an evident prevalence of higher suitable classes of A. artemisiifolia intersecting (i.e., not potentially controlled by) the ones of O. communa . The control that this leaf beetle exerts over the invasive plant is of primary importance because of the problems that A. artemisiifolia causes to agriculture and human health [81,82,83].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, suitable climatic conditions are spread throughout Europe in all time frames considered, even though with an evident prevalence of higher suitable classes of A. artemisiifolia intersecting (i.e., not potentially controlled by) the ones of O. communa . The control that this leaf beetle exerts over the invasive plant is of primary importance because of the problems that A. artemisiifolia causes to agriculture and human health [81,82,83].…”
Section: Discussionmentioning
confidence: 99%
“…Ragweed presence varied considerably and predictably by land use, land use history, cover type, and the presence of pavement and roads. The analysis captured ragweed’s general habitat preferences ( Smith, Cecchi, Skjøth, Karrer, & Šikoparija, 2013 ) and generally matched previous observations of urban ragweed populations ( Katz, Connor Barrie, & Carey, 2014 ; Urbanowicz, Hutyra, & Stinson, 2018 ; Vincent & Bergeron, 1985 ). In particular, the link between building demolition and ragweed presence is well supported; ragweed germination is highest when seeds are at the soil surface ( Pickett & Baskin, 1973 ).…”
Section: Discussionmentioning
confidence: 62%
“…A. artemisiifolia can forms a persistent soil seed bank as a result of complex germination strategies (Essl et al, 2015). The influence of propagule pressure and disturbances on the distribution of A. artemisiifolia is greater than that of environmental factors (Dullinger et al, 2009;Urbanowicz et al, 2018). Kröel-Dulay et al (2019) found that the invasion probability of A. artemisiifolia increases with increasing propagule pressure in continuously disturbed habitats.…”
Section: Introductionmentioning
confidence: 99%